Effects of Naltrexone on Neural and Subjective Response to Alcohol in Treatment‐Seeking Alcohol‐Dependent Patients. (7th January 2015) - Spagnolo, Primavera A.; Ramchandani, Vijay A.; Schwandt, Melanie L.; Zhang, Lishu; Blaine, Sara K.; Usala, Julie M.; Diamond, Kristie A.; Phillips, Monte J.; George, David T.; Momenan, Reza; Heilig, Markus
Abstract : Background: Positively reinforcing properties of alcohol are in part mediated by activation of the ventral striatum (VS). Alcohol‐induced release of endogenous opioids is thought to contribute to this response. Preclinical studies show that the opioid antagonist naltrexone (NTX) can block this cascade, but its ability to do so in treatment‐seeking alcoholics has not been examined. Our objective was to study the effects of NTX on alcohol‐induced VS activation and on amygdala response to affective stimuli in treatment‐seeking alcohol‐dependent inpatients. Methods: Sixty‐three treatment‐seeking alcoholics were randomized to receive NTX (50 mg) or placebo (PLC) daily. On Day 7, participants underwent an alcohol cue reactivity session, and craving was measured using the Penn Alcohol Craving Scale. On Day 9, participants received a saline infusion followed by an alcohol infusion and also viewed affective stimuli in a magnetic resonance scanner. Results: Irrespective of medication treatment condition, the alcohol infusion did not activate the VS in the alcohol‐dependent patients. Unexpectedly, VS activation was greater in NTX treated patients than in the PLC group. NTX treated patients also reported increased craving in response to alcohol cue exposure, and increased subjective response to alcohol ("high" and "intoxicated") compared to PLC subjects. No significant effects of alcohol infusion on brain response to affective stimuli were in the NTX or PLC groups. Conclusions: Unlike previous findings in social drinkers, a moderate level of intoxication did not activate the VS in treatment‐seeking alcoholics. This is likely to reflect tolerance to the positively reinforcing properties of alcohol in this clinical population. Our findings may help explain the efficacy of NTX to reduce heavy drinking, but not to maintain abstinence.